Short-term clinical outcome of stroke patients with or without prior statin treatment - Omid Mirzaee; Abdolhamid Shariat; Faezeh Sehatpour; Mojtaba Neydavoodi; Fatemeh Roozbeh; Seyedeh Shaghayegh Zafarmand; Maryam Owjfard; Shekoofeh Rahimi; Anahid Safari; Afshin Borhani-Haghighi (Shiraz University of Medical Sciences, 2021)
Objective(s): This study evaluated the impact of statin on the severity and outcome of stroke among patients who had taken it prior to the stroke onset and compared to patients who had not received it before the stroke. Methods: We included 261 consecutive patients with acute ischemic stroke who admitted in Namazee hospital affiliated to Shiraz University of Medical Sciences from 2018-2019. We recorded demographic data, vascular risk factors, history of previous statin treatment, and National Institutes of Health Stroke Scale (NIHSS) score at time of hospital admission and modified Rankin Scale (MRS) 3 months after stroke onset. The dependent variables were initial severity of stroke as measured by National Institute of Health Scoring System (NIHSS) and good outcome defined as modified Rankin Scale (MRS) 0 to 1. Results: Among 261 patients with acute ischemic stroke, 76 were using statins (52.6% of users were women). Among all the subjects, 175 (67.6%) had history of hypertension, 78 (30.1%) had history of diabetes mellitus, 87(33.5%) had history of hyperlipidemia, 63 (24.3%) were smokers. Admission NIHSS and MRS were not statistically different in statin users and non-statin users (P= 0.12 and P= 0.08, respectively). Adjusted Odds Ratios for poor functional outcome and 90-day mortality according to previous statin use were 0.87 (95% CI 0.37-2.05), P= 0.54) and 0.75(95% CI 0.31-1.81, P= 0.52) which were not statistically significant. Conclusion: This study showed that pre-stroke statin therapy did not affect the initial clinical severity, short-term functional outcome and 90-day mortality after ischemic stroke.